KE ARAH PENYEDIAAN KAEDAH PENYELIDIKAN HUKUM ISLAM TERKINI: SATU PENGENALAN - Abd Rahim, Rahimin Affandi (Jurnal Syariah, 2019)
Basically this study attempts to explore the notion of Islamic legal research methodology that seems to be needed for the modem world. In order to achieve such objectives, this anicle is designed to be divided into three different sections, firstly, the rationality of modem Islamic legal methodology; secondly, the exposition and clarijacation of the newly proposed Islamic research legal methodology and finally, the supplementary substance for the newly proposed Islamic legal methodology.